Accelerating Religious Tourism in Pioneering Rural Areas: An Aggressive Strategy for Institutional Strengthening and SDG Integration - RM Anto Harprianto; Reiza D Dienaputra; Kevin Muhamad Lukman (International Journal of Research and Community Empowerment, 2026)
Religious tourism holds significant potential to support local economic growth, yet often faces challenges in management and community empowerment. This study aims to analyze the potential of the Sacred Tomb of Buyut Haer in Serang and formulate development strategies based on Community-Based Tourism (CBT) that integrate Sustainable Development Goals (SDGs). The research method employs a descriptive qualitative approach with SWOT analysis, utilizing data from in-depth interviews and field observations. The results indicate that while the site possesses high spiritual value and local wisdom, it suffers from the absence of a formal management body, characterized by a non-existent Tourism Awareness Group (Pokdarwis) and an inactive Village-Owned Enterprise (BUMDes), as well as inadequate basic infrastructure, specifically lacking sanitation facilities and organized parking. To overcome this, an “institution-first” acceleration model is formulated as an Aggressive Strategy (S-O), prioritizing the establishment of inclusive local governance prior to physical investments, alongside developing educational tourism packages integrated with the creative economy and digitalizing promotion. In conclusion, developing pioneering tourism villages requires prioritizing community capacity building and cross-sector collaboration. Ultimately, the implementation of this CBT-based strategy impacts the Sustainable Development Goals by directly generating decent work and economic growth (Goal 8) and fostering inclusive, sustainable rural communities (Goal 11).